Ms. Mentor's impeccable advice for women in academia - Toth, Emily (University of Pennsylvania Press, 1997)
In question-and-answer form, Ms. Mentor advises academic women about issues they daren't discuss openly, such as: How does one really clamber onto the tenure track when the job market is so nasty, brutish, and small? Is there such a thing as the perfectly marketable dissertation topic? How does a meek young woman become a tiger of an authority figure in the classroomand get stupendous teaching evaluations? How does one cope with sexual harassment, grandiosity, and bizarre behavior from entrenched colleagues?